First Human Usutu Virus Reported in Asti (Piedmont, Italy, August 2022) and Early Follow-Up - Tommaso Lupia; Fabio Paolo Marletto; Ilvana Tiziana Scuvera; Roberta Bosio; Barbara Rizzello; Valentina Fornari; Daniela Maria Luisa Vivenza; Valeria Ghisetti; Maria Teresa Brusa; Silvia Corcione; Francesco Giuseppe De Rosa (Tropical Medicine and Infectious Disease, 2022)
The Usutu virus (USUV) has recently attracted the attention of scientists because of its rapid spread across Europe and its growth over the previous seasons in Italy. Here, we describe the first case of USUV infection in Asti, Piedmont region, Italy. The patient remained asymptomatic in the acute phase and during the early follow-up, despite a mild increase in liver enzymes. The prompt diagnosis in this patient was due to positive qualitative PCR for WNV blood-donor screening with negative RT-PCR of WNV and positive USUV-RNA following the confirmation test. Blood-donor screening and transmission risk monitoring are pivotal in following the spread of this Flavivirus in non-endemic countries, due to the high percentage of asymptomatic carriers.